ChemInform Abstract: Palladium‐Catalyzed Synthesis of Isoquinolinones via Sequential Cyclization and N—O Bond Cleavage of N‐Methoxy‐o‐alkynylbenzamides. Issue 25 (3rd June 2013) - Jithunsa, Manita; Ueda, Masafumi; Aoi, Naoki; Sugita, Shoichi; Miyoshi, Tetsuya; Miyata, Okiko
Abstract The method involves the intramolecular addition of Weinreb amides to alkynes followed by N—O bond cleavage and 1, 5‐hydrogen shift as a key step.